Age validation in horse mackerel (Trachurus trachurus) otoliths. - Waldron, Miranda E; Kerstan, Michael (Oxford University Press, 2001)
Two methods were used to validate age determination of horse mackerel otoliths. In the first, whole otoliths were examined with a light microscope. Age was determined by identifying and counting annuli. Marginal increment widths were also measured and served to estimate ages, which ranged from 0.6–4.3 years. In the second method, otoliths were examined with a scanning electron microscope and fish ages were determined by daily increment counts. Sixty-four otolith specimens from the Southeast Atlantic and 24 from the Northeast Atlantic were aged by counting the daily growth increments. The number of daily increments was highly variable within each growth zone. Ages exceeding 365 days in the first annual growth zone indicated that the first annulus was not always deposited in some fish. The variable daily increment counts in the first year's growth zones may be related to the very protracted spawning season of horse mackerel. Examination of subsequent growth zones indicated that false rings and annuli are often of a similar visual appearance and that true annuli can only be identified if concurrent measurements of growth zone widths are available. Estimated ages agreed with ages derived by counting daily increments, thus validating the ages of horse mackerel up to four years.